Performance on neurological development tests by riverine children with moderate mercury exposure in Amazonia, Brazil - Lydia Maria Bocayuva Tavares; Volney Magalhães Câmara; Olaf Malm; Elisabeth C. de Oliveira Santos
The nervous system can be damaged when the population is exposed to methyl mercury (MeHg) by ingesting fish, and children deserve special attention due to their increased susceptibility as compared to adults. A comparative cross-sectional study was performed in order to investigate the use of a battery of neurological development tests in two groups of 209 riverine children from 3 to 7 years old: a group exposed to moderate levels of MeHg (n = 75) and a control group (n = 134). The study included a questionnaire, the collection of scalp hair samples for determination of total mercury concentration, and performance on a test for evaluating neurological function in children. Riverine children presented higher exposure to MeHg (mean hair Hg = 5.37 ± 3.35µg.g-1) in comparison to the control group (mean Hg = 2.08 ± 1.37µg.g-1). Both groups showed a high proportion of children with what was considered "non-normal" performance, suggesting that the results could not be related to mercury exposure and that this type of test presented limitations for use with river-dwelling Amazon communities.